EVALUASI PELAKSANAAN PROGRAM PEMBERDAYAAN DESA (PPD) MELALUI USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) DI KELURAHAN BUKIT KAYU KAPUR KOTA DUMAI TAHUN 2012 - Wahid, Iqbal; Ridwan, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
The research given title “Evaluation Impplementation of The Program economic Enterprises Village saving and Loans (UEK/SP) at Bukit Raya Kapur Village, Dumai City in 2012”. It’s behind of this research is srill a using funds loans not used according to plan the proposal loan lack of aweareness of the public in paying the mortgage in adition it’s still a lot of people who do not in the criteria for low-icome communities also enjoy this program and number of delinquent loans is higher as well the list of loans that are pilling up.The aim of research is evaluation implementation of the program economic enterprises village saving and loans (UEK-SP) at Bukit Raya Kapur Village Dumai City in 2012. The usefulness of this research is as input agencies in an effort to take out policy in the future. Types and method of research is descriptive research, which can be defined as program solving or describe investigated by describing the state of the subject and object of research based on the facts that seem or how their. While the method used qualitative research method to describe the actual situation and the actual detail by looking at the problem and research objectives determined purposive based withdrawal nonprobability sample properties. Data was collected by interview and documentation.The research that concludes evaluation implementation of program economic enterprises village saving and loans (UEK/SP) at Bukit Raya Kapur Village Dumai City in 2012 it’s “Not Good”. Where implementation of the TUPOKSI by UEK/SP has not been done well, so that people who received benefits from this program is not accuarate and this is also due to the implementation of the verification that is not in accordance with existing guidelines so that the level of arrears communities become higher. Arrears by using so the roll can not be done every single month and also resulted in the list of loans the are pilling up. Futhermore, the absorption of funds which have not been up to touch the law-income communities that lack of venture capital.The Key Word : Evaluation, Program, PPD, UEK/SP